Enhancing North Africa’s Infrastructure for Improved Competitiveness - (:unkn) unknown (My University, 2015)
This paper aims at assessing the relationship between infrastructure development and competitiveness in North Africa. Based on the World Bank data, we analyze the infrastructure indicators of four North African countries over the period 1996–2012 and estimate the elasticity of competitiveness with respect to infrastructure development. We ?rst argue that competitiveness could be improved by investing more on infrastructure. Although comparison with sub-Saharan Africa reveals that important progress has been made in North Africa in terms of quantity, countries need to improve the infrastructure quality by investing in green energy, in maintenance, in public private partnerships and in regional infrastructure. Econometric analysis con?rms that a 1 percent increase in infrastructure quality raises competitiveness by 0.64 percent. Country speci?c elasticity is respectively 0.22 in Algeria, 1.42 in Egypt, 0.36 in Tunisia and 0.56 in Morocco. Based on these results, appropriate policy recommendations are discussed.
Keywords: African Research